The Iraqi refugees the new crisis in the Middle East - Sassoon, Joseph (International library of migration studies, 2009)
Since 2003, over 4 million Iraquis have been forced to flee their homes, in what amounts to one of the largest people movements in modern times, far exceeding the Palestinian outflow after 1948. Joseph Sassoon explores the underlying trends of Iraq's refugee flow: which class, ethnic and sectarian groups are going where and how. He analyzes international policy on the refugee issue, and asseses the options for return and resettlement.